Estimation of Traffic Volumes Distribution of Urban Streets in Baghdad City - Ahmed Alkaissi , Zainab; Yousif Hussain, Ruba (Journal of Planner and Development, 2022)
The aim of this research is to explore the time and space distribution of traffic volume demand and investigate its vehicle compositions. The four selected links presented the activity of transportation facilities and different congestion points according to directions. The study area belongs to Al-Rusafa sector in Baghdad city that exhibited higher rate of traffic congestions of working days at peak morning and evening periods due to the different mixed land uses. The obtained results showed that Link (1) from Medical city intersection to Sarafiya intersection, demonstrated the highest traffic volume in both peak time periods morning AM and afternoon PM where the demand exceeds the capacity along the link corridor. Also, higher values for Peak Hour Factor (PHF) were obtained for Link (1) range from (0.88 to 0.94) depending on different peak periods and traffic directions which indicated little flow variation and high traffic volumes. Lower values of PHF were obtained for link (4) (Kasra intersection to Anter square) range from (0.77 to 0.89